Estimation of a Critical Gap/ Lag in Uncontrolled Intersections in Sri Lanka - G. N. Samarasekara; K. S. S. Perera (Journal of South Asian Logistics and Transport)
The critical gap/lag value for an uncontrolled intersection is an important parameter in estimating highway traffic capacity and developing micro stimulations of traffic movements. In manoeuvring an intersection, drivers decide to accept or reject the gap, based on several considerations. However, only a few studies have been carried out to estimate the critical gap on Sri Lankan roads; meanwhile, estimates of external factors are rare. This study found the influence of external factors on drivers’ gap acceptance decision and estimated the critical gap/ lag values using the Binary Logistic model. Analysis considered 4,233 gap acceptance decisions taken by drivers on minor roads. These were collected at three four-way and two three-way intersections and analysed across three vehicle categories: Motorcycle, Threewheeler, and Car/Van. Among the external factors studied, vehicle type, intersection type, size of the available gap, and type of traffic manoeuvre were found to have a significant influence on gap acceptance. Critical gap/lag values found in this study can be used for capacity estimation of three-way and four-way intersections in Sri Lanka.